(untitled) (Indian Journal of Animal Production and Management, 2024)
Nonsyndromic Aplasia Cutis Congenita (Epitheliogenesis Imperfecta) are congenital, circumscribed hypoplastic defects of multiple or deeper skin layers in swine. Although swine have been reported to have epitheliogenesis imperfecta, little is known about this condition in the literature. A new born Large White Yorkshire female piglet was presented with glistening red, well-demarcated discontinuities in the skin on the frontal skull with no apparent bleeding which was managed by conservative treatment.